The Political Effects of Immigration: Culture or Economics? - Alberto Alesina; Marco Tabellini (Institute of Labor Economics (IZA), 2021)
We review the growing literature on the political effects of immigration. After a brief summary of the economics of immigration, we turn to the main focus of the paper: how immigrants influence electoral outcomes in receiving countries, and why. We start from the "standard" view that immigration triggers political backlash and raises support for nativist, anti-immigrant political parties. We present evidence from a variety of studies that the causes of natives' political discontent are unlikely to have (solely) economic roots, but are instead more tightly linked to cultural and social concerns. Next, we discuss works that paint a more nuanced picture of the effects of immigration, which, in some cases, can move natives' preferences in a more liberal direction. We also consider the factors that can explain a seemingly puzzling empirical regularity: the anti-immigration rhetoric has become a banner of right wing parties. We conclude by outlining what, to us, are promising avenues for future research.
Keywords: D72; J11; J15; J61; Z1; 330; immigration; diversity; culture; politics